Peran Penerimaan Teman Sebaya dalam Meningkatkan Kemampuan Bicara Anak dengan Keterlambatan Perkembangan Wicara Anak Usia Dini - Dona Tihnike; Anik Maulidiyah (UIN Sultan Aji Muhammad Idris Samarinda, 2026)
This study aims to analyze peer acceptance and its impact on speech abilities of children with speech development delays at PAUD Al-Muttaqin Plus Kaliondo, Winong, Gempol. The research employs a descriptive qualitative approach with 20 peer children and 5 teachers as subjects. Data collection techniques include interviews, observations, and documentation, with data analysis using the Miles and Huberman model. Results indicate that peer acceptance plays a significant role in improving speech abilities of children with speech delays. Children accepted by peers showed increased confidence, speech frequency, and vocabulary mastery. Peer support provides natural verbal stimulation through daily play interactions. These findings align with Vygotsky's Zone of Proximal Development (ZPD) theory emphasizing the importance of social interaction in language development. The study recommends creating an inclusive learning environment supporting positive peer interactions to accelerate language development in children with special needs.